Third molar tooth agenesis and pattern of impaction in patients with palatally displaced canines - Abu Alhaija, Elham S. (Angle Orthod, 2018)
OBJECTIVES: To investigate the association between third molar agenesis and pattern of impaction, missing teeth, and peg-shaped lateral incisor with palatal canine displacement (PDC). MATERIALS AND METHODS: The pretreatment orthodontic orthopantomograms of 438 patients (122 males and 316 females) diagnosed with PDC were included. A total of 338 patients with normally erupted canines who had a preexisting radiograph as part of their orthodontic treatment (125 males and 313 females) served as controls. Orthopantomograms were evaluated for missing third molars, third molar eruption status, and type of impaction, third molar spaces, third molar width, and angulation. RESULTS: In the PDC group, at least one third molar was missing in 48% and 19% in the upper and lower arches, respectively. Also, 38% and 67% of PDC patients had at least one third molar impaction in the upper and lower arches, respectively. The difference between the PDC and control groups was significant for both missing and impacted third molars (P < .001 for each). The most common type of third molar impaction in the upper arch was vertical and distoangular in the PDC and control groups, respectively. Upper and lower third molar width and spaces were reduced in PDC patients when compared with the control group (P < .001). In PDC patients, missing teeth and peg-shaped lateral incisors were recorded in 5.6% and 9.1%, respectively. CONCLUSIONS: PDC patients showed a high prevalence of third molar agenesis and impaction. Upper and lower third molar width and space were reduced in the PDC patients. There were no significant associations between tooth agenesis (other than third molars) and the PDC anomaly.